Using phrase-frames to trace the language development of L1 Chinese learners of English. (August 2022) - Tan, Yi; Römer, Ute
Abstract: A recent trend in corpus-based research emphasizes the importance to examine repeated, discontinuous word sequences in addition to continuous ones. The present study extends this trend into research on the use of phrase-frames (repeated word sequences with variable slots, e.g., it is * to ) and their variants (e.g., important, easy ) in a large corpus of L1 Chinese learner writing in English across five proficiency levels. Phrase-frames were automatically identified based on established frequency and range thresholds and manually filtered for meaningfulness. The analysis focuses on differences in the variability, predictability, and functions of the 100 most frequent phrase-frames (of spans three and four) across levels. The results revealed that, as learners move to more advanced proficiency levels, they tend to employ phrase-frames that are more variable and less predictable. Results also indicate that the functions expressed by high-frequency phrase-frames vary between proficiency levels. This study contributes to a better understanding of the process of L2 learners' development of phraseological competence.